Lightening Effect of Skin Lightening Cream Containing Piper betle L. Extract in Human Volunteers - Omar, Sharifah Shakirah Syed; Hadi, Hazrina; Mohd Hanif, Nadzira; Ahmad, Hawa Mas Azmar; Ng, Shiow-Fern (Cosmetics (Basel), 2021)
Hyperpigmentation affects people globally with negative psychological impacts. Piper betle L. leaf (PBL) extract has many benefits including skin lightening which may reduce hyperpigmentation. The objective of this study was to develop an effective skin-lightening cream containing PBL with ideal characteristics. A formulation of base cream and PBL cream was prepared and characterized by centrifugation, particle size and zeta potential analysis, rheological profile studies and physical properties’ observation. In vivo studies on 30 human subjects tested the effects of base and PBL cream on skin-lightening, hydration, trans-epidermal water loss (TEWL) and elasticity through weekly tests 4 weeks in duration. Base and PBL creams had a non-Newtonian property with acceptable color, odor, texture, zeta potential, particle size and showed no phase separation. The in vivo study indicated a significant reduction in melanin content and an improvement in skin tone for PBL cream but not in base cream. TEWL and elasticity also showed significant reduction for both formulations, indicating a healthier skin barrier and supple skin with consistent use, although hydration fluctuated with no significant changes. The developed PBL cream showed significant results in the reduction in melanin content and improving skin tone, which shows the formulation can confer skin-lightening effect.